2009
DOI: 10.2133/dmpk.24.557
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations in the HGPRT, ITPA, IMPDH1, IMPDH2, and GMPS Genes in Japanese Individuals

Abstract: Thiopurines (such as azathioprine and 6-mercaptopurine) are widely used for the treatment of patients suffering from malignancies, rheumatic disease, inflammatory bowel disease and solid organ transplant rejection. These drugs are activated and eliminated by a number of enzymes in the human body. This analyzes all the exons and exon-intron junctions of 5 enzyme genes (hypoxanthine-guanine phosphoribosyltransferase, HGPRT; inosine triphosphate pyrophosphatase, ITPA; inosine monophosphate dehydrogenases 1 and 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Here, we showed that ITPA and IMPDH2 were both upregulated DEGs related and may be related to the observed trend of increased IMP. ITPA functions in nucleotide binding, Nicotinamide adenine dinucleotide pyrophosphatase activity, and deoxyinosine triphosphate diphosphatase activity, and also participates in deoxyribonucleoside triphosphate catabolic processes, nucleoside triphosphate catabolic processes, and ITP catabolic processes (Kudo et al., 2009; Sakumi et al., 2010). Additionally, IMPDH2 is a key gene in the rate‐limiting step of de novo guanine nucleotide synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we showed that ITPA and IMPDH2 were both upregulated DEGs related and may be related to the observed trend of increased IMP. ITPA functions in nucleotide binding, Nicotinamide adenine dinucleotide pyrophosphatase activity, and deoxyinosine triphosphate diphosphatase activity, and also participates in deoxyribonucleoside triphosphate catabolic processes, nucleoside triphosphate catabolic processes, and ITP catabolic processes (Kudo et al., 2009; Sakumi et al., 2010). Additionally, IMPDH2 is a key gene in the rate‐limiting step of de novo guanine nucleotide synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…In normal cells, inosine diphosphate and inosine triphosphate are produced from inosine monophosphate by kinases, and ITPA preferentially catalyses hydrolysis of inosine triphosphate back to inosine monophosphate and pyrophosphate, to prevent the accumulation of 6‐thioinosine triphosphate (6‐TITP), rogue nucleotides, which would be otherwise incorporated into DNA and RNA, or compete with nucleotides . Recently, SNPs in the ITPA gene, some of which are accompanied by decreased enzyme activity, have been reported . The most frequent SNPs related with deficient ITPA activity are 94C>A and IVS2 + 21A>C .…”
Section: Resultsmentioning
confidence: 99%
“…When this PhD project started, a few studies concerning varying enzyme activity or the connection between varying genotypes and adverse reactions in other thiopurine metabolizing enzymes had been published. Throughout these years, the complexity of thiopurine metabolism has been more extensive with reports of several polymorphisms within the metabolism of thiopurines (ITPA [166,167], HGPRT [142,168], IMPDH [168][169][170], XO [60,171], GST [172][173][174], GMPS [168], Rac1 [175], NT5C2 [176,177], PACSIN2 [178], genes in the mismatch repair system (MMR) [179], folate cycle [152][153][154] and transporters [56,175,[180][181][182]) and recently, pharmacogenetic testing of NUDT15, whose variants are more common in Asian populations, has been implemented in the guidelines of the Clinical Pharmacogenetics Implementation Consortium (CPIC) for thiopurine treatment [19,183] . Otherwise, so far, no other polymorphism has had the same extensive effect on thiopurine treatment as the genetic variants of TPMT.…”
Section: Discrepancies and Factors Influencing The Activitymentioning
confidence: 99%